Vehicle pedestrian collisions: Validated models for pedestrian Impact and Projection - SIMMS, CIARAN KNUT (Sage, 2005)
The most important factor in pedestrian injuries from vehicle collisions is the impact velocity. In cases where the impact configuration can be ascertained, the most common method now used to determine vehicle speed involves the pedestrian projection distance. The more traditional method of using tyre brake marks is losing applicability as ABS braking systems become more common. The two most common impact configurations are wrap projection and forward projection, these being determined by the vehicle/pedestrian geometry and the initial conditions of the impact. In this paper, two models are presented for pedestrian forward and wrap projection impacts. These models are predicated on separating the total projection distance into the individual projection distances occurring during three principal phases of the collision. The models are novel as they use a rigid single-segment body representation of the pedestrian, include explicit modelling of the impact phase, and also allow for uncertainty in the input parameters. Published data are used to provide distributions for the input variables such as pedestrian and vehicle masses, etc. The model predictions of impact speed from overall projection distance are validated by comparison with real-world accident data.
PUBLISHED
Keywords: Public and environmental health; vehicle collisions